Exotics and Wildlife : A manual of veterinary nursing care - Gosden, Caroline (Edinburgh : Butterworth-Heinemann, 2004)
This manual provides a hands-on approach to nursing exotic pets and wildlife common to the UK. It links with the current S/NVQ syllabus, informing, preparing and teaching the veterinary nurse to deal with the variety of species they are likely to see in practice.
Includes index.
Keywords: Exotic animals -- Diseases -- Nursing; Veterinary nursing; Farming and Country Life